Penguatan Dan Pengembangan Keberlanjutan Usaha Umkm Dari Aspek Usaha Dan Kelembagaan Desa Karangturi – Karanganyar - Setyaningtyas Honggowati; Bambang Hadinugroho; Endang Suhari; Heru Agustanto; Yohana Tamara; Harmadi Harmadi (Dikmas: Jurnal Pendidikan Masyarakat dan Pengabdian, 2023)
Indonesian MSMEs are the largest in number compared to those in other developing countries. However, the progress of Information Technology in MSMEs is perceived to be below expectations. Based on the conducted testing in the village of Karangturi, Karanganyar, the lack of responsiveness of MSMEs to technological advancements is attributed to their low entrepreneurial spirit and motivation. Therefore, there is a need to strengthen and enhance the sustainability of MSMEs, addressing both business and institutional aspects. The Faculty of Economics and Business, UNS, will provide support and development in entrepreneurship, with motivational materials, business model canvas, and creativity in business. Equipping MSMEs with knowledge from successful business actors in IT and social media is expected to instill enthusiasm for advancing their businesses and overcoming challenges.